2021
DOI: 10.1080/16078454.2021.1948208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating clonal plasma cells in newly diagnosed multiple myeloma

Abstract: Objectives: Multiple myeloma (MM) involves a clinically and biologically heterogeneous malignancy of plasma cells. It is difficult to predict the prognosis of MM. The presence of circulating clonal plasma cells (CPC) has been associated with a worse prognosis in patients with MM. Methods: This study retrospectively analysed CPC in 108 newly diagnosed MM patients by 8colour flow cytometry to investigate their value for predicting the outcome and combined the level of CPC with the revised International Staging S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Several authors have demonstrated that the presence of circulating plasma cells in peripheral blood is a prognostic biomarker that could be used for risk stratification in MM [32][33][34][35][36]. We, therefore, wanted to analyze this parameter in our series, in the context of anti-CD38 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that the presence of circulating plasma cells in peripheral blood is a prognostic biomarker that could be used for risk stratification in MM [32][33][34][35][36]. We, therefore, wanted to analyze this parameter in our series, in the context of anti-CD38 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of blood or BM were stained with antibodies to CD19, CD27, CD38, CD45, CD56, CD138, cLambda and cKappa, and cells were subsequently detected by 8-color flow cytometry to quantify CPC and BMPC. Details of the flow cytometry technique for CPC and BMPC detection have been described in our previous studies ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chromosomal abnormalities (CAs) play a significant role for predicting the risk of patients with MM. CMMC levels were correlated with a higher incidence of high-risk cytogenetic abnormalities [6,13,20,27,28,34,63,[70][71][72], a lower incidence of hyperdiploidy [26], and standard-risk cytogenetic abnormalities [34]. CMMC abundance was associated with disease burden in the BM, including the tumor cell involvement [6, 7, 13, 14, 20, 23-25, 28, 33, 34, 39, 63, 70, 71] and the myeloma clone levels of Ig rearrangements in the BM [44].…”
Section: Disease Burden Assessmentmentioning
confidence: 99%